The impact of influenza A virus protein phosphorylation and host cell protein kinases on viral replication - Liu, Lu; Justus Liebig University Giessen (My University, 2022)
This work is divided into two parts, which both address the relevance of phosphorylation events induced by the IAV infection. The first part of the study addressed the functional relevance of kinases activity in IAV-infected cells, which regulate the phosphorylation occurring on cellular proteins. With this regard, PamStation® platform-based analysis of Ser/Thr kinases or Tyr kinases present in IAV-infected cells, was performed to compare the kinase activation patterns triggered by the human circulating IAV isolate A/Hamburg/4/09 (H1N1pdm09) and the highly pathogenic avian IAV human isolate A/Thailand/1(KAN-1)/2004 (H5N1). The results indicate that the Tyr phosphorylations of substrate peptides were largely co-regulated by both viruses and are also strongly overrepresented in comparison to Ser/Thr peptide phosphorylations. It allowed to identify 26 of 47 predicated kinases, which are mainly strain-specific and have been implicated in the IAV life cycle, while the function of other 21 kinases on IAV infection is unknown. Subsequently, the perturbation of selected novel kinases with highly specific small molecule inhibitors or siRNAs was conducted to investigate the relevance of these kinases. Received data revealed negative regulation of H1N1pdm09 and H5N1 replication by NUAK (novel (nua) kinase) kinases, redundant ephrin A (EphA) receptor Tyr kinases and a H1N1pdm09-selective pro-viral function of JAK3 (Janus kinase 3). The second part of this study was performed to characterize the relevance of phosphorylation occurring on proteins encoded by the IAV strain SC35M (H7N7). For this I integrated all phosphorylations on viral proteins that have been previously detected in our laboratory, together with those found in other literature, along with information on their intramolecular localization in possible functional domains and/or with a suggested relevant function. The subsequent functional analysis focused on phosphorylation sites, which are evolutionally highly conserved, not functionally described but with important functional implications. Based on mutational analysis results of five phosphorylation sites of PB2 (T471), PA (Y393, S393), NP (Y148, T378), three phosphorylation sites of NS1 (S48, T49, T197), and one phosphorylation site of M1 (T108), three distinct groups of phosphorylation effects could be assigned. The first group of phosphorylations does not have a direct physiological consequence, as reflected by PB2 T471 and NS1 T197, for which neither their phospho-deficient nor phospho-mimetic mutation affects viral replication of SC35M in MLE-15 cell culture. The second group of phosphorylations has a modulatory function, which is exemplified by PA S395 and NS1 ST48, 49. Here, either a phospho-deficient mutation or a phospho-mimetic mutation slightly alters the viral replication. Of particular interest is the third group of phosphorylations showing a critical role in viral replication. For example, the phospho-mimetic mutation for the vRNP components PA (Y393E), NP (Y148E, T378E), and for the phospho-deficient M1 T108A mutation, which all prevent the production of infections virus. Further functional analysis of selected phosphorylations revealed their distinct biological roles. As such, constitutive phosphorylation on PA Y393 and S395 inhibits polymerase functions to transcribe and replicate the viral genome, which partially also holds true for the phospho-mimetic mutation at NP Y148, which also impaired polymerase activity. Although an inhibitory effect on viral propagation was also seen for the phospho-memetic mutation at NP T378, a different mechanism must be expected, as this mutation leads to an increased polymerase activity. With regard to the M1 T108 phosphorylation, the experimental results point to the requirement of this phosphorylation for viral propagation via controlling the nuclear M1 import and nuclear vRNP export. Furthermore, a study applying intracellular chemical crosslinking of M1 protein complexes indicates that M1 T108 phosphorylation might avoid excess of M1 polymerization, which may be critical for maintaining conformational flexibility of M1 to switch between assembly and disassembly during viral replication. Further M1 interactome studies revealed a possible role of M1 T108 phosphorylation in regulating protein/protein interaction. This approach disclosed a network of proteins from the STRIPAK complex, in particular its core components STRN/STRN3, acting as novel interacting partners of M1 protein, with preferential binding affinity to WT M1. Loss-of-function experiments also indicate that STRN/STRN3 function as pro-viral factors supporting IAV replication. Moreover, immunofluorescence studies showed the IAV infection led to slight cytoplasmic accumulation of STRN and larger aggregates formation of STRN3. Collectively, the functional characterization of PA Y393, S395, and NP Y148 phosphorylation on the activity adds new examples for phosphorylation-regulated RNP activity. On the other hand, the identification of virus-supportive phosphorylation M1 T108 and its combinatorial pro-viral interactors could provide new insights into therapeutic interference with IAV replication
Keywords: influenza A virus; kinase; polymerase; matrix protein 1; phosphorylation; STRIPAK; ddc:570